PERCEIVED VALUE DIMENSIONS OF SHOPPING TOURISM - Ratna Roostika (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
Superior customer value is essential to win competition. The perception of customer value has grown in interest since it has been found to have stable impacts on satisfaction, behavioral intentions and ultimately business performance. Considering that the most common definition of perceived value refers to the trade-off between benefits and sacrifices, thus, this study adopts the second-order formative conceptualization of perceived value and examined its links to satisfaction and loyalty. Four main tourist shopping locations in Yogyakarta were used to collect the data. By applying Partial Least Squares to test the model in the tourism shopping context, the results indicate that perceived value has positive relationships with satisfaction and loyalty. Additionally, it was found that the total contribution of perceived value and satisfaction on loyalty were only small.